2011
DOI: 10.1016/j.optmat.2011.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Electron paramagnetic resonance study of rare-earth related centres in K2YF5:Tb3+ thermoluminescence phosphors

Abstract: Rare-earth related centres have been investigated in K 2 YF 5 :Tb 3+ crystals, exhibiting thermoluminescence (TL) below and above room temperature (RT), using electron paramagnetic resonance (EPR) spectroscopy at Q (34 GHz) and W-band (94 GHz). The spectra have been studied prior to irradiation, after exposure in the kGy range to X-rays at 77 K and subsequent pulse annealing up to 570 K. In addition to Gd 3+ , previously studied in detail, we identified Er 3+ and Yb 3+ centres as accidental impurities in as-gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In principle, this result implies that no optical quenching effects related to the increase of the dopant concentration seem to be present in this fluoride. The reason for this observation could be related to the fact that Tb cations replace Y atoms with minimum lattice distortion (Zverev et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…In principle, this result implies that no optical quenching effects related to the increase of the dopant concentration seem to be present in this fluoride. The reason for this observation could be related to the fact that Tb cations replace Y atoms with minimum lattice distortion (Zverev et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…In this context it is worth mentioning that the role played by rare-earth cations doped into K 2 YF 5 have been studied by electron paramagnetic resonance (EPR) experiments. In particular, Zverev et al (2011) identified at least three radiation-induced paramagnetic centers in K 2 YF 5 :Tb 3þ , which are Tb-related, say, their EPR signal does not show up in nominally pure K 2 YF 5 . They also found that Tb 3þ doped in K 2 YF 5 captures a hole during irradiation to form Tb 4þ .…”
Section: Discussion Of Experimental Resultsmentioning
confidence: 99%
“…They also found that Tb 3þ doped in K 2 YF 5 captures a hole during irradiation to form Tb 4þ . Zverev et al (2011) concluded that some of these hole traps could be associated with a nearby unknown defect compensating the effective charge þe of Tb 4þ at an Y 3þ site. By taking into account the results reported by Dorenbos et al (2011) the same behavior could be expected for Pr 3þ doped into K 2 YF 5 .…”
Section: Discussion Of Experimental Resultsmentioning
confidence: 99%